Advanced fabrication process for combined atomic force-scanning electrochemical microscopy (AFM-SECM) probes. (January 2015) - Eifert, Alexander; Mizaikoff, Boris; Kranz, Christine
Highlights: We present a semi-automated fabrication process for combined atomic force-scanning electrochemical microscopy probes. An advanced software-controlled focused ion beam (FIB) patterning enables milling at reduced fabrication time. Different insulation materials are evaluated in terms of their influence on the electrochemical behavior. Combined AFM-SECM imaging with top-milled combined probes is successfully demonstrated. Abstract: An advanced software-controlled focused ion beam (FIB) patterning process for the fabrication of combined atomic force-scanning electrochemical microscopy (AFM-SECM) probes is reported. FIB milling is a standard process in scanning probe microscopy (SPM) for specialized SPM probe fabrication. For AFM-SECM, milling of bifunctional probes usually requires several milling steps. Milling such complex multi-layer/multi-material structures using a single milling routine leads to significantly reduced fabrication times and costs. Based on an advanced patterning routine, a semi-automated FIB milling routine for fabricating combined AFM-SECM probes with high reproducibility is presented with future potential for processing at a wafer level. The fabricated bifunctional probes were electrochemically characterized using cyclic voltammetry, and their performance for AFM-SECM imaging experiments was tested. Different insulation materials (Parylene-C and Si x N y ) have been evaluated with respect to facilitating the overall milling process, the influence on the electrochemical behavior and the long-term stability of the obtained probes. Furthermore, the influence of material composition and layer sequence to the overall shape and properties of the combined probes were evaluated.